The Impact of Turkey's Natural Gas Distribution Tender Process on the Current Deficit - Tunçsiper, Çağatay; Özdemir, Cebrail (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The main factors that increase the energy demand of countries are the rate of ownership of energy resources and their level of development. Since Turkey is a developing country and does not have sufficient energy resources, it is a net foreign-dependent country in energy. In this study, the factors that increase the natural gas demand in Turkey due to the neo-liberal economic policies implemented in the recent period and the effects of the increasing demand on the balance of payments are examined. Turkey's natural gas distribution tenders in recent years have further increased the foreign dependency ratio in energy, which is already at a high level. To make the economic development sustainable, it is of great importance to ensure the current account balance, which is the most important item in the balance of foreign payments. The demand for natural gas, which is one of the most important import items of Turkey, which aims to develop in the economy, cannot be met by domestic resources, so the balance of payments is adversely affected. With this study, it has been revealed that there is a causal link between the increasing natural gas demand in our country and the current account deficit, which cannot be closed.